“It's Just More Acceptable To Be White or Mixed Race and Gay Than Black and Gay”: The Perceptions and Experiences of Homophobia in St. Lucia - Couzens, Jimmy; Mahoney, Berenice; Wilkinson, Dean (Frontiers in Psychology, 2017)
Lesbian, gay and bisexual (LGB) individuals come from diverse cultural groups with differing ethnic and racial identities. However, most research on LGB people uses white western samples and studies of Afro-Caribbean diaspora often use Jamaican samples. Thus, the complexity of Afro-Caribbean LGB peoples’ experiences of homophobia is largely unknown. The authors’ analyses explore experiences of homophobia among LGB people in St. Lucia. Findings indicate issues of skin-shade orientated tolerance, regionalized disparities in levels of tolerance towards LGB people and regionalized passing (regionalized sexual identity shifting). Finally, the authors’ findings indicate that skin shade identities and regional location influence the psychological health outcomes of homophobia experienced by LGB people in St. Lucia.